2013
DOI: 10.1007/s10067-013-2443-8
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra treatment in drug-resistant Behcet’s disease: a case series

Abstract: The study objective was to report treatment with an interleukin (IL)-1 receptor antagonist, anakinra, in patients with multiorgan Behcet's disease (BD). Comparison of clinical manifestations, previous treatments, markers of inflammation, concomitant medications, treatment regimen modifications, relapses, and adverse events before and during anakinra administration among patients with BD were evaluated. Nine BD patients (mean age 34.55 ± 16.30 years) refractory to tumor necrosis factor blockers and standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 38 publications
1
79
0
3
Order By: Relevance
“…A proof-of-concept study by Güll et al strongly implicated IL1β and BD with significant improvement seen especially in patients with uveitis treated with IL1β-regulating antibody [47]. Recently Tugal-Tutkun et al demonstrated rapid control of uveitis in BD patients without the need for high-dose corticosteroid in a prospective, open-label, randomized phase II trial [48] supporting several other previous studies of the proven efficacy of IL1β to induce stable clinical remission among BD patients [49][50][51][52].…”
Section: The Interleukin-1 (Il1) Family: Il1β Il18 Il33mentioning
confidence: 68%
See 1 more Smart Citation
“…A proof-of-concept study by Güll et al strongly implicated IL1β and BD with significant improvement seen especially in patients with uveitis treated with IL1β-regulating antibody [47]. Recently Tugal-Tutkun et al demonstrated rapid control of uveitis in BD patients without the need for high-dose corticosteroid in a prospective, open-label, randomized phase II trial [48] supporting several other previous studies of the proven efficacy of IL1β to induce stable clinical remission among BD patients [49][50][51][52].…”
Section: The Interleukin-1 (Il1) Family: Il1β Il18 Il33mentioning
confidence: 68%
“…Evidence from the GWASs further implicated several cytokines underlying the pathogenesis of BD [17,18,[22][23][24][25][26]. Moreover, the successful use of various anti-cytokine therapies in BD patients provides additional evidence that cytokines play a crucial role in its pathogenesis [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. These overall observations highlight the fundamental role of cytokines as key players in the pathogenesis of BD.…”
Section: The Cytokines Network Of Bdmentioning
confidence: 99%
“…Недавно было обнару-жено увеличение экспрессии P2X7-рецепторов на моно-цитах пациентов, что способствует увеличению высвобо-ждения ИЛ1β из этих клеток [134]. В ряде исследований продемонстрирована высокая эффективность анакинры [135][136][137][138][139][140], канакинумаба [141,142] и гевокизумаба [143] у пациентов с болезнью Бехчета. Особые надежды возла-гают на гевокизумаб, лечение которым приводит к быст-рой положительной динамике увеита и симптомов пора-жения ЦНС.…”
Section: синдром шницлераunclassified
“…Thus, official EULAR recommendations propose their use for refractory cases (grade 3C and 3D) [150]. Additionally, recently published small case series of patients with BD treated with tocilizumab and anakinra also include some patients with neuro-BD, and the results were encouraging [19,158].…”
Section: Behçet's Disease (Bd)mentioning
confidence: 99%